Cities at the Front Lines of Development - Wolfowitz, Paul (2016)
Paul Wolfowitz, President of the World Bank, stated that the importance of cities is increasing on a daily basis. By 2030, China alone will add 342 million new urban residents, and India 271 million. Africa will add 395 million people and more than half (54 percent) of its population will be living in urban areas. Urbanization creates job opportunities and poverty challenges. Urbanization has place mayors on center stage to implement solutions to alleviate poverty at the local level. The World Bank established a dedicated urban unit more than 30 years ago, with estimated lending on urban issues in 2005 at $7 billion. The Bank looks forward to strengthening partnerships with local governments.